A STUDY ON NEXT GENERATION PAYMENT SYSTEM (Forum for Linguistic Studies, 2024)
This paper explores the key features and advancements that characterize these innovative systems. However, challenges such as security risks, privacy concerns, and regulatory complexities need to be addressed to ensure secure and inclusive adoption. By fostering collaboration between stakeholders, we can unlock the full potential of next-generation payment systems, offering faster, more secure, and accessible financial solutions. Biometric authentication enhances security and streamlines user experience. The exploration of block chain technology fosters decentralization and transparency. Real-time settlements empower users with immediate fund access. The next-generation payment system represents a transformative paradigm shift in the realm of financial transactions, introducing cutting-edge technologies to redefine the way we conduct payments in the digital age. Mobile payments have gained significant traction, providing users with seamless transactions via smart phones. Crypto currencies have emerged as alternative payment options, challenging traditional financial norms